Exploiting PLGA-Based Biocompatible Nanoparticles for Next-Generation Tolerogenic Vaccines against Autoimmune Disease - Cappellano, Giuseppe (Int J Mol Sci, 2019)
Tolerogenic vaccines are aimed at inhibiting antigen-specific immune responses. Antigen-loaded nanoparticles (NPs) have been recently emerged as ideal tools for tolerogenic vaccination because their composition, size, and capability of loading immunomodulatory molecules can be readily exploited to induce peripheral tolerance. Among polymeric NPs, poly(lactic-co-glycolic acid) (PLGA) NPs have the advantage of currently holding approval for several applications in drug delivery, diagnostics, and other clinical uses by the Food and Drug Administration (FDA). PLGA-NPs are non-toxic and display excellent biocompatibility and biodegradability properties. Moreover, surface functionalization may improve their interaction with biological materials, thereby optimizing targeting and performance. PLGA-NPs are the most extensively studied in pre-clinical model in the field of tolerogenic vaccination. Thus, this review describes their potential applications in the treatment of autoimmune diseases.